GISAXS analysis of Ge nanoparticles embedded ZnO thin films: The effect of oxygen partial pressure and thermal process on the nanostructured aggregations. (15th November 2017) - Çınar Bam, Begüm; Ide, Semra; Keilbach, Andreas; Ceylan, Abdullah
Abstract: Ge nanoparticles embedded in ZnO thin films (synthesized on p-type Si substrates) were investigated to explore their potential usage possibilities as diodes for opto-electronic devices and photovoltaics, thin-film transistors, and solar cells. Nano scale structural details under the effect of different gas pressure of O2 may include some hints to understand and develop structure-property correlations of the focused type materials. With this purpose, GISAXS (Grazing-incidence small-angle X–ray scattering) was used for 3D structural analysis of the films according to the thermal process (Rapid Thermal Annealing: RTA and Absence of Thermal Effect: AS-MADE) and O2 partial pressure during the deposition of ZnO matrix. As a result of the study, it may be said that size and shape controlled growth processes are possible for these types of films. Especially, increase in pressure indicates orthogonal like prismatic morphology at 1 mTorr, cylindrical at 3 mTorr and more compact spherical formation at 5 mTorr. That way, morphology controlled nanoscale growth can be achieved by changing the oxygen partial pressure for the oxide matrices. On the other hand, size of the nano aggregations decreases with increased partial pressure for both of RTA processed and AS-MADE samples. Decreasing ratio in the size of AS-MADE sample is bigger than that of RTA samples. Graphical abstract: